Explaining the Causes of Hidden Marital Aggression in Women: The Role of Feelings of Guilt and Self-Sufficiency - Heidari, Elaheh; Shirazi, Mahmood; Sanagoi Mohrer, Gholamreza (Psychology of Woman Journal, 2022)
The purpose of the present study was to explain the cause of hidden marital aggression in women with the mediating role of guilt and self-compassion. The method of the present research was applied in terms of objective and descriptive data collection method with correlation method. Structural equation model is used in researches where the goal is to test a specific model of prediction between variables. The statistical population of the research was married women working in the Broadcasting Organization of the Islamic Republic of Iran in Tehran. In this research, a multi-stage random sampling method was used and 150 married women were selected by simple random sampling. They responded to covert marital communication aggression, Nelson and Carroll (2006), self-compassion, Reiss (2011), and conscious affect, Tangeney, Wagner, and Gomez (1989). Pearson’s correlation coefficient and path analysis were used for analysis. The results of data analysis showed that self-compassion affects guilt (β=0.49, P=0.01). In addition, self-compassion affects the covert aggression of marital communication (β=0.32, P=0.01) and the effect of self-compassion on the covert aggression of marital communication. These effects have a significant relationship with the mediation of guilt (β=0.16, P=0.01). According to the obtained results, guilt can play a mediating role between hidden aggression in marital relationship and self-compassion in married women.